167k views
0 votes
1. Solve by graphing:
4x + y = 4
3x – y = 3​

User Drathier
by
5.1k points

2 Answers

2 votes

☽------------❀-------------☾

Hi there!

~

Answer:

A)
y = -4x + 4

______________|

B)
y = 3x + -3

______________|

❀Hope this helped you!❀

☽------------❀-------------☾

User Naan
by
5.3k points
1 vote

Answer:

y = -4x+4

y = 3x-3

Explanation:

First equation subtract 4x from both sides

Second equation deduct 3x both sides, then multiply both sides by a negative

1. y = -4x+4

2. y= 3x-3

User Limitlessriver
by
5.1k points